2020
DOI: 10.1371/journal.pone.0242573
|View full text |Cite
|
Sign up to set email alerts
|

Game-based learning environments affect frontal brain activity

Abstract: Inclusion of game elements in learning environments to increase motivation and learning outcome is becoming increasingly popular. However, underlying mechanisms of game-based learning have not been studied sufficiently yet. In the present study, we investigated effects of game-based learning environments on a neurofunctional level. In particular, 59 healthy adults completed a game-based version (including game elements such as a narrative and virtual incentives) as well as a non-game-based version of a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 91 publications
(161 reference statements)
3
27
0
Order By: Relevance
“…Although several scales have been used to measure flow experience in game-based learning [15], in the present study we use the Flow Short Scale [68], because it has been successfully used in several game-based learning studies in the mathematics domain [66 67], [69], [70] and in some studies, its subscales, fluency of performance and absorption by activity, are analyzed [69], [70] allowing a more fine-grained basis for examining the relation between flow experience and situational interest. For instance, Ninaus et al [70] found a game-based version of a math task as compared to its non-game-based equivalent to achieve higher scores on fluency of the performance subscale.…”
Section: Measuring Engagement In Game-based Learningmentioning
confidence: 99%
“…Although several scales have been used to measure flow experience in game-based learning [15], in the present study we use the Flow Short Scale [68], because it has been successfully used in several game-based learning studies in the mathematics domain [66 67], [69], [70] and in some studies, its subscales, fluency of performance and absorption by activity, are analyzed [69], [70] allowing a more fine-grained basis for examining the relation between flow experience and situational interest. For instance, Ninaus et al [70] found a game-based version of a math task as compared to its non-game-based equivalent to achieve higher scores on fluency of the performance subscale.…”
Section: Measuring Engagement In Game-based Learningmentioning
confidence: 99%
“…This confirms prior research findings that moderate online games can improve players' cognitive executive ability ( 28 , 29 ) and alleviate or even reduce players' anxiety, depression, and other negative emotions ( 30 , 31 ). A brain electrophysiology study on games also showed that moderate games activate brain areas related to emotion processing and that the frontal lobe areas related to attention are also more activated ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also outline a detailed and practical framework for use in such games, elements of which can be applied to eventdriven games in an academic setting. In another study, Koberid et al [15] presented a framework for achieving flow in educational games. Their work links educational theory with game design and validates to maintaining engagement in educational games.…”
Section: Related Workmentioning
confidence: 99%